Emergence of perceptuomotor relationships during paleolithic stone toolmaking learning: intersections of observation and practice - Kristel Yu Tiamco Bayani (Nature Portfolio, 2021)
In order to evaluate changes and relationships in perceptual process during motor learning and motor performance over training, Bayani et al examine eye movements and motor skill in a paleolithic stone toolmaking task. They demonstrate the importance of understanding the emergence and evolution of perceptual-motor coupling not only in complex motor skill learning.